Pension confusion, uncertainty and trust in Scotland: an empirical analysis - Webb, Rob; Watson, Duncan; Ring, Patrick; Bryce, Cormac (Cambridge University Press, 2014)
In the context of the new auto-enrolment requirements for employers to make pension provision for their employees, and the importance of trust in pension provision, this article utilises data from the Scottish Social Attitudes Survey which in its 2005 wave asked correspondents specific questions regarding pension provision. We integrate two different empirical approaches in order to achieve a more robust understanding of pension confusion in Scotland. We find that pension confusion is dominated by pension uncertainty and myopia but may be reduced by working in the financial services sector. We consider the implications of these findings for the relationship of trust between employers and their employees, as well as for government pension policy more generally.